1992
DOI: 10.1017/s0033291700038502
|View full text |Cite
|
Sign up to set email alerts
|

Posed facial expressions of emotion in schizophrenia and depression

Abstract: It is generally agreed that schizophrenia patients show a markedly reduced ability to perceive and express facial emotions. Previous studies have shown, however, that such deficits are emotion-specific in schizophrenia and not generalized. Three kinds of studies were examined: decoding studies dealing with schizophrenia patients' ability to perceive universally recognized facial expressions of emotions, encoding studies dealing with schizophrenia patients' ability to express certain facial emotions, and studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 45 publications
(90 reference statements)
4
30
0
Order By: Relevance
“…The schizotypy group reported smells as subjectively less pleasant than controls, indicating that there is a difference for the at-risk group in comparative emotional experience. Interestingly, and consistent with prior studies (see Minor & Cohen, 2010, for a review), patients with schizophrenia do not generally show reduced hedonic experience of olfactory stimuli in the laboratory (Berenbaum, 1992). Thus, there appears to be a discrepancy regarding experience in patients with schizophrenia and those with psychometrically defined schizotypy.…”
Section: Discussionsupporting
confidence: 78%
“…The schizotypy group reported smells as subjectively less pleasant than controls, indicating that there is a difference for the at-risk group in comparative emotional experience. Interestingly, and consistent with prior studies (see Minor & Cohen, 2010, for a review), patients with schizophrenia do not generally show reduced hedonic experience of olfactory stimuli in the laboratory (Berenbaum, 1992). Thus, there appears to be a discrepancy regarding experience in patients with schizophrenia and those with psychometrically defined schizotypy.…”
Section: Discussionsupporting
confidence: 78%
“…Examinations of facial expressions beyond clinical rating scales in schizophrenia have reported on imitative expressions (Putnam and Kring, 2007; Schwartz et al, 2006; Tremeau et al, 2005), deliberate or posed expressions (Berenbaum, 1992; Schwartz et al, 2006; Tremeau et al, 2005), spontaneous expressions within dyadic interactions (Aghevli et al, 2003; Mattes et al, 1995; Schneider et al, 1990; Steimer-Krause et al, 1990), expressions associated with emotional film clips ((Berenbaum and Oltmanns, 1992; Earnst et al, 1996; Kring et al, 1999, 1993) or emotional experiences of the participants (Berenbaum and Oltmanns, 1992; Gottheil et al, 1970; Kring et al, 1993; Tremeau et al, 2005). Media for capturing facial expressions have included still photographs (Gottheil et al, 1976; Schwartz et al, 2006), videotapes (Aghevli et al, 2003; Berenbaum, 1992; Berenbaum and Oltmanns, 1992; Gaebel and Wolwer, 2004; Kring et al, 1993; Putnam and Kring, 2007; Steimer-Krause et al, 1990; Tremeau et al, 2005), and electromyographic recordings (Earnst et al, 1996; Kring et al, 1999; Mattes et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Media for capturing facial expressions have included still photographs (Gottheil et al, 1976; Schwartz et al, 2006), videotapes (Aghevli et al, 2003; Berenbaum, 1992; Berenbaum and Oltmanns, 1992; Gaebel and Wolwer, 2004; Kring et al, 1993; Putnam and Kring, 2007; Steimer-Krause et al, 1990; Tremeau et al, 2005), and electromyographic recordings (Earnst et al, 1996; Kring et al, 1999; Mattes et al, 1995). Videotaped acquisition offers the advantage of capturing duration and frequency of emotion expressions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, longitudinal research has shown that as youth move through adolescence, they experience a greater level of negative emotions and report a lower level of happiness than at other points during the life span (Larson et al, 2002). Low levels of positive affect and high negative affect have been associated with poor psychological functioning, general distress and dysfunction, depression, and anxiety (Berenbaum, 1992). Tragically, in dealing with difficult emotions and changing social interactions, a large number of adolescents turn to suicidal behavior as the way to deal with mounting despair.…”
mentioning
confidence: 99%